When the Cat's Away: A Content Analysis of MNC Overseas Recruitment Print Ads - LEONG, Siew Meng (Institutional Knowledge at Singapore Management University, 2004)
This study examines discrimination in the overseas recruitment print ad of Multinational National Corporations (MNC) in a lax regulatory environment, Singapore. Institutionalization theory suggests that in a weakly regulated environment, MNC affiliates would tend to adopt the less stringent requirements. With the lack of a strong legal framework in the host country, the home country's legal and cultural imperative would be more alien, suggesting differences in discrimination as a function of home country imperatives. Some 1122 recruitment print ads of US, UK, and Japanese affiliates of MNCs were examined. While discrimination was found in the print ads of all organizations, US affiliates were least discriminatory, followed by Japan, and UK affiliates. When Singapore firms were included, they were found to be least discriminatory. However, Singapore firms became more discriminatory when the request for a recent photograph was considered in the discrimination index. Implications of the findings are discussed and suggestions for future research advanced.